Haunted - Martin, Kat (Kensington Publishing Corp, 2024)
1898: Robbery, prostitution, and violence are commonplace in the fabulously rich copper mining city of Jerome, Arizona. But a brutal murder sets the stage for a series of strange events that will echo far into the future. 2024: Jenny Spencer's Copper Star Saloon and Hotel is one of the best-loved attractions in the popular tourist destination, but eerie occurrences in the newly renovated wing are souring business. Cain Barrett, the wealthy owner of the nearby Grandview Hotel, has his eye on Jenny. He'll help her any way he can, but Cain has problems of his own... A brutal murder at the Copper Star, entries in a dusty journal, and ghostly sightings at both hotels... is the connection a figment of Jenny's imagination, or a threat to her life? And who is causing trouble for Cain? As they work together to solve the mystery, Cain vows not to let anything, or anyone--living or dead--stand between him and the woman he has come to love. --